2019
DOI: 10.1016/j.jtumed.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of satisfaction and internet self-efficacy of inquirers using an internet-based drug information centre

Abstract: Objectives This study aimed to evaluate the satisfaction level of inquirers of an internet-based drug information centre along with the internet usage abilities and habits of individuals who had previously utilised services from an internet-based drug information centre in Turkey. Methods The first 100 individuals who received medication consultancy from the webpage entitled “ www.ilacpedia.com ” and consented to participate in the study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Moreover, a total of 990 counselling services were also provided by the clinical pharmacist through WPCS regarding proper medication use, proper treatment duration, required refilling of prescription and/or OTC medication, proper dosage selection and proper drug alternative. Furthermore, the information provided by an online pharmacy consultation service were understandable by 93% of the participants and 83% of them were satisfied with the answers provided and consultations offered by the pharmacists 25 . Accordingly, these emphasise the essential role of the pharmacists for the provision of appropriate counselling services and a well‐defined education and counselling to diminish and prevent many DRPs; thereby improve patient's care and outcomes 35‐37 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, a total of 990 counselling services were also provided by the clinical pharmacist through WPCS regarding proper medication use, proper treatment duration, required refilling of prescription and/or OTC medication, proper dosage selection and proper drug alternative. Furthermore, the information provided by an online pharmacy consultation service were understandable by 93% of the participants and 83% of them were satisfied with the answers provided and consultations offered by the pharmacists 25 . Accordingly, these emphasise the essential role of the pharmacists for the provision of appropriate counselling services and a well‐defined education and counselling to diminish and prevent many DRPs; thereby improve patient's care and outcomes 35‐37 .…”
Section: Discussionmentioning
confidence: 97%
“…Unlike participants with university level education, those with primary/secondary education level more visited WPCS for health‐related concerns in comparison to other concerns indicating this concern as high priority for this group of participants. Umefjord et al 24 and Izzettin et al 25 found that women used the internet as a counselling service more than men did. In keeping with the literature, approximately 90% of the women in all European Union countries aged between 16 and 29 years have used the internet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toplum eczacılarıyla yapılan bir çalışmada ürün bulunurluğunu tespit etme, ilaç fiyatları, ilaçlar ve hastalıklarla ilgili bilgilere ulaşma amacıyla eczacıların günde birden fazla kez interneti kullandığı ortaya konmuştur [12]. İnternetten sağlık bilgilerine olan talep artışı ile eczacıların internet üzerinden verdiği danışmanlık hizmetlerinin önem taşıdığı, bir internet sayfasından klinik eczacılar tarafından sağlanan ilaç danışmanlığı hizmetinden kullanıcıların memnun kaldığı belirtilmektedir [14]. Ayrıca internet tabanlı öğrenme, sürekli eczacılık eğitimi için de uygun bir ortam olarak kabul edilmektedir [15].…”
Section: Introductionunclassified